Glass Reinforced Concrete (GRC) - Lisa Khusna Hendrawati; Roudotul Magfiroh Ariada; Denny Oktavina R (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Background: Glass Reinforced Concrete (GRC) is an innovative construction material that combines glass fiber with concrete, providing high strength and durability. However, the influence of GRC mixture composition on flexural strength values has not been studied in depth. Therefore, this study aims to analyze the effect of GRC mixture composition variables, such as the ratio between glass fiber and concrete binder, on flexural strength. It is hoped that the results of this research can provide deeper insight into the use of GRC in construction and help develop more efficient and durable construction materials. Results: From the results of the discussion regarding the effect of differences in fiberglass composition on flexural strength, it was found that the addition of 2% fiber resulted in an average flexural strength of 23.01 kgf/cm2, with an increase of up to 49.77 kgf/cm2 at 1% fiberglass. However, with a fiber composition of 0.8%, the highest flexural strength was obtained at 56.84 kgf/cm2. The addition of fibers that exceed the maximum limit can reduce the density of GRC concrete so that its ability to distribute bending strength forces is reduced. Meanwhile, the effect of fly ash substitution on flexural strength shows that replacing some of the cement with fly ash by 20% can increase the flexural strength value of GRC, because the silica and alumina compounds in fly ash can speed up the hydration process. However, of the five specimens tested, none met the SNI 8299:2017 standard which requires a minimum average flexural strength of 100 kgf/cm2